2018
DOI: 10.1016/j.juro.2017.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Local Tumor Bed Recurrence Following Partial Nephrectomy in Patients with Small Renal Masses

Abstract: Local tumor bed recurrence after partial nephrectomy is associated with several preoperative factors, including multiple tumors and a solitary kidney, as well as intraoperative and postoperative factors such as a positive surgical margin and higher pathological stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 22 publications
0
28
0
10
Order By: Relevance
“…RN radical nephrectomy, PN partial nephrectomy, BMI body mass index, DM diabetes mellitus, HTN hypertension, ECOG Eastern cooperative oncology group performance status, MDRD modification of diet in renal disease, GFR estimated glomerular filtration rate, R radius (maximal diameter), E exophytic/endophytic, N nearness to collecting duct system/renal sinus, A anterior/posterior location, L location relative to the polar lines. www.nature.com/scientificreports/ follow-up imaging or (2) the detection of a new enhancing lesion in the same region of the ipsilateral kidney as the original PN site (e.g., the PN site and the recurrence site were both in the lower pole) 6 . Systemic recurrence was defined as tumor development at systemic distant sites or in non-regional retroperitoneal LNs 8 .…”
Section: Openmentioning
confidence: 99%
See 1 more Smart Citation
“…RN radical nephrectomy, PN partial nephrectomy, BMI body mass index, DM diabetes mellitus, HTN hypertension, ECOG Eastern cooperative oncology group performance status, MDRD modification of diet in renal disease, GFR estimated glomerular filtration rate, R radius (maximal diameter), E exophytic/endophytic, N nearness to collecting duct system/renal sinus, A anterior/posterior location, L location relative to the polar lines. www.nature.com/scientificreports/ follow-up imaging or (2) the detection of a new enhancing lesion in the same region of the ipsilateral kidney as the original PN site (e.g., the PN site and the recurrence site were both in the lower pole) 6 . Systemic recurrence was defined as tumor development at systemic distant sites or in non-regional retroperitoneal LNs 8 .…”
Section: Openmentioning
confidence: 99%
“…Nevertheless, 20-40% of the patients treated for the localized case were reported to have recurrences 5 . In a multicenter study, Shah et al observed that the disease recurred in 5.6% of the patients treated with PN for clinically localized RCC 6 . With the number of PN increasing in the last few years, growing attempts have been made to implement PN even for high complex renal tumors described by RENAL nephrometry score (RENAL), developed as a useful evaluation tool for predicting operative complexity posed by warm ischemic time (WIT) or postoperative complications 7 .…”
mentioning
confidence: 99%
“…Larger tumors (median 4.1 cm) and higher clinical stage at presentation (cT3 or greater) are associated with local tumor bed recurrence, both of which were present in this patient. 5 It is fitting that a similar risk stratification profile would predict disease recurrence in cases of concomitant UTUC.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно данным мировой литературы, случаи ре-цидива рака почки после выполнения резекции почки колеблются от 0 до 10,6 % [7][8][9][10]. В нашем исследо-вании местные рецидивы после проведенных ЛРП при сроке наблюдения от 3 до 71 мес (в среднем 8,6 мес) [11].…”
Section: Discussionunclassified